Does CHA2DS2-VASc Score Predict MACE in Patients Undergoing Isolated Coronary Artery Bypass Grafting Surgery? - Kalyoncuoglu,Muhsin (2019)
Abstract Objective: To evaluate the prognostic value of CHA2DS2-VASc score in individuals undergoing isolated coronary artery bypass grafting (CABG) surgery. Methods: Records of consecutive 464 patients who underwent elective isolated CABG, between January 2015 and August 2017, were retrospectively reviewed. A major adverse cardiac event (MACE) was the primary outcome of this study. MACE in patients with low (L) (<2, n: 238) and high (H) (≤2, n: 226) CHA2DS2-VASc scores were compared. Univariate logistic regression analysis identified preditors of MACE. Results: Hypertension, diabetes mellitus, and peripheral vascular disease were more frequent in the H group than in the L group. European System for Cardiac Operative Risk Evaluation (EuroSCORE) I and SYNTAX I scores were similar in both groups while SYNTAX II-CABG score was significantly higher in the H group than in the L group. Postoperative myocardial infarction, need for intra-aortic balloon pump, acute renal failure, and mediastinitis were more frequent in the H group than in the L group. The H group had significantly higher in-hospital mortality and MACE rates than the L group (P<0.01). EuroSCORE I, SYNTAX II-CABG, and CHA2DS2-VASc scores were predictors for MACE. SYNTAX II-CABG > 25.1 had 68.4% sensitivity and 52.7% specificity (area under the curve [AUC]: 0.653, P=0.04, 95% confidence interval [CI]: 0.607-0.696) and CHA2DS2-VASc > 2 had 52.6% sensitivity and 84.1% specificity (AUC: 0.752, P<0.01, 95% CI: 0.710-0.790) to predict MACE. Pairwise comparison of receiver-operating characteristic curves revealed similar accuracy for both scoring systems. Conclusion: CHA2DS2-VASc score may predict MACE in patients undergoing isolated CABG.